Determination of Ions and Iron Content in Hydatid Cysts of Echinococcus Granulosus Isolated From Different Intermediate Hosts (Sheep, Goats, Cattle and Human) Tissues - Mero, Wijdan M.S.; Meerkhan, Azad A. (Science Journal of University of Zakho, 2014)
This study included comparative biochemical composition of hydatid fluid, protoscolices, infected and non-infected tissues isolated from liver and lungs of infected sheep, goats, and cattle in Duhok abattoirs during the period from Nov. 2009 to Apr. 2010. Also hydatid fluid of cysts surgically removed from humans in Azadi Teaching Hospital, Duhok during the period from Mar. 2010 to Jul. 2010.Hydatid cysts and host tissues were analyzed for Ions (Na+, K+, Ca++, and Mg++) and Fe++. Among Ions, Na+ exhibited high levels in hydatid fluid of the studied hosts with the highest being in hydatid fluid of sheep liver cyst (356±8.207 mg/dl); furthermore, infected tissues showed higher Na+ levels with the highest being in sheep liver and lung tissues (196±7.461 and 178±5.868 mg/100g respectively). Protoscolices of both liver and lungs showed high K+ levels, among tissues, infected tissue contained high K+ levels with the highest being in infected lung tissues (Ranged from 63.46±0.597 mg/100g to 77.39±0.729 mg/100g). Nearly similar levels of Ca++ were detected in hydatid fluid and protoscolices of all cysts with the highest level being in goats cysts protoscolices (Liver: 9.212±0.081 mg/100g, Lungs: 9.044±0.072 mg/100g) and the lowest in cattle cysts fluid (Liver: 6.954±0.061 mg/dl, Lungs: 6.826±0.054 mg/dl). The level of Mg++ was low in hydatid cysts and tissues of all hosts (Ranged from 0.746±0.016 mg/100g to 0.952±0.015). Small quantities of iron were detected in hydatid cysts of all hosts which were higher in cattle liver cysts (Hydatid fluid 0.0882±0.003 mg/dl and protoscolices 0.0838±0.003 mg/100g) and infected liver tissues (0.2293±0.008 mg/100g).